An Empirical Study on Capital Structure Choice in SMEs: Evidence from Company Panel Data - Wu, Xinru (2019)
With the coming of the 21st century, the world economy is developing rapidly. Along with the vigorous development of economy, many the small and medium-sized enterprises (SMEs) with flexibility and creativity have obtained the broad space for survival and development. Whether in the developed countries or developing countries, these SMEs play an increasingly important role. At present, many SMEs are in the transition stage of growth to maturity, and it is more crucial for them to optimize the capital decision. This paper tries to sum up the thesis of capital structure, as well as the influence factors of capital decision choice, applied fixed effect model with a dataset of SMEs from North America during 2008 to 2017. This paper uses leverage ratio as a dependent variable to examine its relationship to company size, age, fixed asset ratio, growth opportunities, profitability, cash flow, and credit rating. The findings illustrate that the capital structure decisions of 1,982 SMEs in North America are aligned with the prediction of the pecking order theory. In addition, except for company age, the remaining explanatory variables are positively related with the debt ratio of company.